Implementasi Media Wordwall dalam Pembelajaran Teks Biografi Kelas X-7 SMA Negeri 11 Semarang: Implementation of Wordwall Media on Learning Biography of SMA Negeri 11 Semarang - Laviolla Putri Mahendra; Ngatmini Ngatmini (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Education is an activity carried out by adults consciously and responsibly towards children with the aim of creating interactions that influence students so they can adapt to their environment. Learning is an essential process for every individual. In learning situations, teachers are responsible for creating a fun learning environment and actively involving students. The activeness of learning participants is influenced by various things, including teacher creativity in using learning methods. One solution to increase students' active learning is to use learning media, such as wordwall. Wordwall is a web-based educational game platform that teachers can use to create quizzes and interactive games in the learning process. The use of wordwall is expected to make learning more interesting, increase student participation, and enrich the learning experience. The aim of this research is to observe the level of activity of class X-7 students after implementing wordwall media in learning Biographical Texts at SMA Negeri 11 Semarang. By focusing on the use of wordwall, this research will explain the impact of this media on students' participation and active learning. The research method used is descriptive qualitative which aims to describe events that occur in learning biographical texts in class X-7. Data was collected through observation, interviews and documentation from class X-7 students. This research used a purposive sampling technique in taking samples so that one class sample was selected based on class division during PPL I activities. The results of the research showed that there was an impact of implementing wordwall media for students in class X-7, namely students looked active, enthusiastic, able to answer questions asked by the teacher, and the class felt fun.